Estimated Daily Intake and Seasonal Food Sources of Quercetin in Japan - Nishimuro, Haruno; Ohnishi, Hirofumi; Sato, Midori; Ohnishi-Kameyama, Mayumi; Matsunaga, Izumi; Naito, Shigehiro; Ippoushi, Katsunari; Oike, Hideaki; Nagata, Tadahiro; Akasaka, Hiroshi; Saitoh, Shigeyuki; Shimamoto, Kazuaki; et al. (Nutrients, 2015)
Quercetin is a promising food component, which can prevent lifestyle related diseases. To understand the dietary intake of quercetin in the subjects of a population-based cohort study and in the Japanese population, we first determined the quercetin content in foods available in the market during June and July in or near a town in Hokkaido, Japan. Red leaf lettuce, asparagus, and onions contained high amounts of quercetin derivatives. We then estimated the daily quercetin intake by 570 residents aged 20–92 years old in the town using a food frequency questionnaire (FFQ). The average and median quercetin intakes were 16.2 and 15.5 mg day−1, respectively. The quercetin intakes by men were lower than those by women; the quercetin intakes showed a low correlation with age in both men and women. The estimated quercetin intake was similar during summer and winter. Quercetin was mainly ingested from onions and green tea, both in summer and in winter. Vegetables, such as asparagus, green pepper, tomatoes, and red leaf lettuce, were good sources of quercetin in summer. Our results will help to elucidate the association between quercetin intake and risks of lifestyle-related diseases by further prospective cohort study and establish healthy dietary requirements with the consumption of more physiologically useful components from foods.